2022
DOI: 10.3390/en15218164
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Slurry Diffusion Law of Fluidized Filling Gangue in the Caving Goaf of Thick Coal Seam Fully Mechanized Caving Mining

Abstract: Because of the problem of gangue discharge and surface subsidence during coal mining, the current research on underground filling mainly focuses on the paste filling, solid filling, and grouting filling of the overburden separation layer after scaffolding. We proposed the technology of fluidization gangue grouting for filling the collapse area based on our previous research. The prediction method of residual space in the collapse area and the diffusion law of gangue fluidization filling slurry are two essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…For the slow-flowing slurry in geomaterials, the momentum due to inertia is negligible [1,[9][10][11][12]. Meanwhile, the momentum exchange owing to the mass transfer of slurry to solid phase is also considered small and is neglected, having the same order of magnitude as the inertial momentum terms.…”
Section: Momentum Balance Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the slow-flowing slurry in geomaterials, the momentum due to inertia is negligible [1,[9][10][11][12]. Meanwhile, the momentum exchange owing to the mass transfer of slurry to solid phase is also considered small and is neglected, having the same order of magnitude as the inertial momentum terms.…”
Section: Momentum Balance Equationsmentioning
confidence: 99%
“…However, three-dimensional or in situ tests are more suitable for evaluating cement-based slurry grouting implemented in fieldworks [4]. Scholars have proposed many numerical Mathematics 2023, 11, 2877 2 of 14 analysis [5][6][7][8] or analytical methods [9][10][11][12][13][14][15] to explore the migration mechanism of cementbased slurry grouting in geomaterials. The common disadvantage of these models is that they cannot reflect the hydro-mechanical dynamic coupling between the force acting on the solid skeleton of geomaterials and the migration of suspended slurry particles.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the distribution law of remaining space is important for filling effects. He simulated coal gangue slurry diffusion in goaf using COMSOL simulation software and found that “cavity-pore” multi-type residual spaces gradually expand [ 4 ]. In addition, researchers have also studied the effects of major fissures in fracture networks and slurry viscosity on diffusion, developed dynamic water-injection grouting simulation experimental devices for fractured rock masses.…”
Section: Introductionmentioning
confidence: 99%
“…2 Well and Huangling No. 2 Well [37,38], and there is no relevant research on shallow buried and kilometer mine. When the GGFSS is applied in the mine with different buried depths, the suitable grouting hole layout is different.…”
Section: Introductionmentioning
confidence: 99%